A fluorescent chitosan hydrogel detection platform for the sensitive and selective determination of trace mercury(ii) in water. Issue 38 (27th August 2015) - Geng, Zhigang; Zhang, Haimin; Xiong, Qizhong; Zhang, Yunxia; Zhao, Huijun; Wang, Guozhong
Abstract : A fluorescent chitosan hydrogel detection platform was developed by cross-linking chitosan fibers with glutaric dialdehyde (GD) fluorophores, exhibiting superior performance for the sensitive and selective determination of trace Hg 2+ in water. Abstract : In this work, a three-dimensional (3D) chitosan hydrogel with superior fluorescence properties was successfully fabricated by modifying chitosan fibers with glutaric dialdehyde (GD) via a simple cross-linking approach. The resulting three-dimensional fluorescent chitosan hydrogel (3D-FCH) with hydrophilic properties exhibited a strong blue fluorescence emission at an excitation wavelength of 337 nm. The fluorescence mechanism of the as-synthesized 3D-FCH was investigated and proposed in detail using X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FT-IR) techniques. As a solid-phase fluorescent probe, the 3D-FCH was used to selectively and sensitively determine mercury(ii ) (Hg 2+ ) ions in aqueous media. The results demonstrated that a prominent fluorescence quenching at 401 nm was observed in the presence of Hg 2+ with a linear response range of 5.0–50 nM and an estimated limit of detection of 0.9 nM. The fluorescence quenching mechanism could be ascribed to the strong complexation between Hg 2+ and the GD fluorophore with a conjugate structure. Moreover, the porous structure of the chitosan hydrogel and the high adsorption capacity of the chitosan fibers in the hydrogel could be very favorable for the rapid fluorescence determination of Hg 2+ . This work may pave a new way to develop low-cost fluorescent chitosan hydrogels as solid-phase fluorescence determination platforms to replace traditional liquid-phase fluorophores for application in the fluorescence detection of heavy metal ions.